Analysis of The Factors Affecting Household Consumption Expenditure in the Fishing Community of Ponjalae, Palopo City - Petra, Petra (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The importance of understanding household consumption expenditure in fishing communities, particularly those influenced by local economic dynamics, socio-cultural characteristics, and access to resources. This study aims to identify the factors affecting household consumption expenditure in the fishing community of Ponjalae, Palopo City. The type of research conducted is qualitative descriptive research. The research location was at the Fish Auction Place (TPI) in Palopo City. The selection of informants in this study used purposive sampling technique, which is based on certain criteria. To collect data, the researcher used several methods, including in-depth interviews to gather information about consumption expenditure patterns, participant observation to understand their consumption patterns and social interactions, and documentation in the form of field notes or photos that support the observation results. Data validity was obtained through data triangulation, which involved verifying information gathered from interviews, observations, and document references. The data analysis method used was thematic analysis, which involves data reduction, data presentation, and drawing conclusions, with the aim of providing a clear picture of the factors influencing household consumption expenditure in the fishing community. The results of the study show that the household consumption expenditure of fishermen in Ponjalae is heavily influenced by income fluctuations related to fishing seasons, the number of family members, as well as broader socio-economic factors. Income fluctuations play a decisive role in managing consumption expenditure, while social and cultural factors play an important role in how expenditures are managed.